PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO EXPLAINER UNTUK MENINGKATKAN PEMAHAMAN PESERTA DIDIK PADA MATERI KEBERAGAMAN MASYARAKAT INDONESIA - Gilang Muhammad Akbar; Mohamad Abduh; Sri Rumiati (Universitas Sultan Ageng Tirtayasa, 2026)
This study aims to develop a video explainer–based learning media on the topic of Indonesian societal diversity within the framework of Bhinneka Tunggal Ika and to examine its effectiveness in improving students’ understanding and tolerance attitudes. The research employed a Research and Development (R&D) approach using the Borg and Gall development model. The study was conducted at SMPIT Al-Izzah, Serang Regency, involving 39 ninth-grade students as research subjects. The instruments used included expert validation sheets, cognitive understanding tests, tolerance attitude questionnaires, teacher and student response questionnaires, and observation sheets. Quantitative data were analyzed using descriptive statistics and gain score analysis, while qualitative data were analyzed descriptively. The results showed that the developed video explainer learning media was categorized as very feasible based on material experts, media experts, and learning experts validation results. The implementation of the media significantly improved students’ understanding, indicated by an increase in the average pretest score from 57.9 to 83.8 in the posttest. Furthermore, the tolerance attitude questionnaire results indicated that students’ tolerance attitudes were in the good category, reflected in indicators such as respect for differences, cooperation, polite communication, and acceptance of diverse backgrounds. The study concludes that video explainer–based learning media is effective in enhancing students’ conceptual understanding and fostering tolerance attitudes in Pancasila and Citizenship Education learning